IMPLEMENTASI PELATIHAN MICROSOFT POWERPOINT SEBAGAI UPAYA PENINGKATAN KUALITAS PRESENTASI DI SMKN 1 ARJASA - Fatimah Isa Auliya; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
The advancement of technology, especially through the use of applications like Microsoft PowerPoint, has transformed the way educational materials are delivered, facilitating the development of communication and visual design skills. PowerPoint is a software designed specifically to present multimedia programs in an engaging way. Using PowerPoint presentations is a method to introduce or explain various topics that are summarized and packaged into several slides, which may include text, images, graphics, sound, and video. The use of PowerPoint not only helps students prepare presentations but also enhances communication and visual design skills, making the presentation process more engaging and effective in conveying information. In the environment of SMK Negeri 1 Arjasa, PowerPoint is a crucial tool in improving students' skills that are relevant to the workforce and enriching the learning process in the digital era. Furthermore, the use of PowerPoint also supports the visualization of material, enabling the presentation of information in a visually appealing way, which captures the audience’s attention and maintains students' interest during learning.